Elastic properties of tyres affecting car comfort, driving and riding - Dechkova, Silvia (Zielona Góra: Uniwersytet Zielonogórski)
The present paper focuses on an elastic properties analysis of new and depreciated tires. The research was carried out using two different methods, field and numerical, respectively. The purpose of the study is to check whether there is a change in the elastic properties of the tire during its depreciation and to what extent these processes affect the comfort of driving and riding.
Keywords: FEM; ABAQUS; SolidWorks; hydraulic test stand; rubber elasticity